Listener judgments of speaker and speech traits of varieties of Asian English. Issue 8 (14th September 2019) - Hansen Edwards, Jette G.; Zampini, Mary L.; Cunningham, Caitlin
ABSTRACT: This study examines language attitudes towards different varieties of English through listener judgments of speaker and speech traits; in addition, the study explores the relationship of these judgments to the intelligibility, as well as the perceived accentedness and comprehensibility, of varieties of Asian English and General American English. While a great deal of research has examined the intelligibility, accentedness, and comprehensibility of English, including varieties of Asian English, no research to date has examined the relationship between language attitudes and the aforementioned dimensions of Asian English speech. That is, little is known about how listeners' judgments regarding speaker and speech traits relate to intelligibility, as well as how such judgments relate to the way in which the listener evaluates the accentedness and comprehensibility of the speaker's speech. The current study addresses these issues through an examination of listener reactions to three varieties of Asian English (Hong Kong English, Singapore English, and China English), as well as American English.